2016
DOI: 10.1289/ehp182
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Tributyltin Chloride on Cybrids with or without an ATP Synthase Pathologic Mutation

Abstract: Background:The oxidative phosphorylation system (OXPHOS) includes nuclear chromosome (nDNA)– and mitochondrial DNA (mtDNA)–encoded polypeptides. Many rare OXPHOS disorders, such as striatal necrosis syndromes, are caused by genetic mutations. Despite important advances in sequencing procedures, causative mutations remain undetected in some patients. It is possible that etiologic factors, such as environmental toxins, are the cause of these cases. Indeed, the inhibition of a particular enzyme by a poison could … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 8 publications
(3 citation statements)
references
References 50 publications
0
3
0
Order By: Relevance
“…The AmpFLSTR ® Identifiler ® PCR Amplification Kit (Life Technologies) was used to determine the cybrids nDNA genetic fingerprints. The molecular cytogenetic analysis was done according to already published procedures (Lopez-Gallardo et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AmpFLSTR ® Identifiler ® PCR Amplification Kit (Life Technologies) was used to determine the cybrids nDNA genetic fingerprints. The molecular cytogenetic analysis was done according to already published procedures (Lopez-Gallardo et al, 2016).…”
Section: Methodsmentioning
confidence: 99%
“…We have previously suggested that mtDNA genetic background in the cytochrome b gene might affect the interaction with pesticides or pharmaceutical drugs (Gomez-Duran et al, 2011). Moreover, we found that mtDNA genetic variation modifies the off-target effects of ribosomal antibiotics used to fight pathogenic bacteria (Pacheu-Grau et al, 2013), and that the widely distributed pollutant tributyltin chloride, an ATP synthase inhibitor, modified the phenotypic effects caused by a pathological mtDNA mutation (Lopez-Gallardo et al, 2016). Thus, considering the interaction between mtDNA and environment factors is going to be important to explain the pathogenicity of mitochondrial disease due to mtDNA mutations.…”
Section: Figmentioning
confidence: 96%
“…Another possibility is that the effect of an accumulation of mildly deleterious variants may only become clinically significant once a population is challenged by a rapid change of confounding factors, such as diet or other environmental factors (toxins). 126 , 127 …”
Section: Current Approaches Used For Investigating Mtdna Involvement mentioning
confidence: 99%